Assessment of Preparedness of Government of Nepal in COVID Designated Hospitals and Clinics for Pandemic Response - Gyanwali , Pradip; Bista, Navindra Raj; Khadka , Mira; Vaidya , Anju; Mahato , Namra Kumar; Karn , Mukesh Kumar; Pant , Suman; Ghimire , Namita; Pokhrel , Anil; Dhimal , Meghnath (Journal of Nepal Health Research Council, 2021)
Background: Preparedness, readiness, and response status of any country is integral in identifying, managing, and preventing COVID-19 pandemic. The objective of this study is to assess the status of the Government of Nepal designated COVID hospitals and COVID clinics to respond against COVID-19. Methods: A cross sectional study was conducted with the focal persons of COVID hospitals and COVID clinics using a semi-structured questionnaire from April 26, 2020 to May 27, 2020 via face to face interview with onsite observation and telephonic interview in few unreachable health facilities. Results: Government of Nepal designated COVID hospitals and COVID clinics demonstrated efforts in establishing preparedness plans and committees such as COVID management core team (96.7% and 86%), provision of coordination with the government authority (both 100% ), preparedness response plan (93.3% and 84%), and infection prevention and control committee (63.3% and 65.6%) to respond to COVID-19 respectively. The participants reported differences in training provided to their health care workers with maximum COVID hospitals (80%) providing training on use of personal protective equipment and least (43.3%) on handling dead bodies. Only half of the COVID clinics (49.5%) had provision of triage systems. Conclusions: COVID hospitals and COVID clinics in Nepal demonstrated different status of COVID pandemic preparedness and readiness. In case of surge, Nepalese hospitals would struggle due to lack of trained workforce and infrastructure. Interdisciplinary, multi-sectoral collaboration with various focused strategies, including in-service training to staff, is paramount to increase preparedness and readiness. Keywords: COVID-19; Nepal; preparedness; readiness